The Protective Effects of Silver Fluoride Solution and Fluoride Varnish on Dental Erosion—An In Vivo Study - Julie Marie Haabeth Brox; Amela Tulek; Amer Sehic; Aida Mulic; Tor Paaske Utheim; Qalbi Khan (Dentistry Journal)
Objectives: Dental erosion has evolved into a common condition with growing concern in the dental community. The aim of this study was to explore the protective effects of two highly fluoridated products, silver fluoride solution (silver diamine fluoride-potassium iodide solution, SDF-KI) and fluoride varnish, on dental erosion in mouse. Methods: Two groups of ten young CD-1 mouse were given a cola drink ad libitum over a 6-week period. A prophylactic treatment with a silver fluoride solution (38% SDF 48,000 ppm F with a silver concentration of 253,900 ppm) and a fluoride varnish (NaF, 22,600 ppm F) were applied on the mandibular molars, performed under sedation twice a week during the whole experiment. Furthermore, two control groups of ten mice were included, a positive (cola drink) and a negative (distilled water) control. A terminal procedure was followed by dissection of mandibular molars and analysis of them using scanning electron microscopy (SEM). The first molars were transversely ground, further analyzed by SEM, and measured for tooth height and tooth tissue loss. Results: Analyses of mandibular molars treated with a fluoride varnish indicated a 5% decreased tooth tissue loss, compared to the molars which served as a positive control. The best effect was achieved with the application of silver fluoride solution, displaying a 35% decreased tooth tissue loss compared to the positive control group. Conclusions: Preventive treatment with a solution of silver fluoride solution exhibits greater protection against dental erosion compared to a traditional fluoride varnish. This study indicates that silver fluoride solution is an effective fluoride compound and is highly beneficial in a clinical setting with the aim of preventing dental erosion.